MAKNA ESTETIK PANTUN PERNIKAHAN MELAYU DELI - Fatimah Sari Siregar; Edy Suprayetno (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2017)
The purpose of training and accompaniment of Deli Melayu pantun especially at Malay wedding event can keep preserving Malay culture deli especially pantun in marriage adat marriage can be maintained and can able to improve personality of Malay society especially young Malay ladies Deli and public become more polite and more polite person. Melayu Deli Malay traditional ceremony, each pantun expresses meaning and meaning that is very depth. Workshop, training and accompaniment carried out in this activity. Deli deli marriage weddings have the meaning of advice to the bride and groom, delivered in beautiful language and polite. From the results of training and accompaniment marriage deli pantun Melayu Deli youth to see that they already understand the form of rhymes, how to create and write pantun, and the meaning contained in pantun.